Strongyloidiasis: A Diagnosis to Consider in Previously Endemic Regions in Portugal - Pinto, Joel (2021)
Strongyloides stercoralis is a parasite capable of surviving for decades in a single host, due to its ability of auto-infection. Strongyloidiasis usually presents a chronic and asymptomatic evolution, and isolated eosinophilia, cutaneous or gastrointestinal abnormalities are the most frequent findings. Between the 1910s and 1980s, several cases of autochthonous strongyloidiasis in Portugal have been described. We report the case of a patient with abdominal pain, ascites and marked eosinophilia. The diagnostic investigation excluded frequent causes of eosinophilia. The diagnosis of strongyloidiasis was confirmed by immunoenzymatic positivity of the antibody to Strongyloides stercoralis. Since the patient lived in a region where several cases of strongyloidiasis were diagnosed in the past, and given the absence of previous trips abroad, this is the first case identified in recent decades of autochthonous strongyloidiasis in Portugal. The authors point out the possibility of chronic infection acquired in regions previously considered foci of great endemicity.